2023
DOI: 10.1038/s41598-023-34808-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomics of oral squamous cell carcinomas based on NMR and MS approaches provides biomarker identification and survival prediction

Abstract: Metabolomics has proven to be an important omics approach to understand the molecular pathways underlying the tumour phenotype and to identify new clinically useful markers. The literature on cancer has illustrated the potential of this approach as a diagnostic and prognostic tool. The present study aimed to analyse the plasma metabolic profile of patients with oral squamous cell carcinoma (OSCC) and controls and to compare patients with metastatic and primary tumours at different stages and subsites using nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“… 52 Sarcosine has been implicated in promoting the malignant proliferation of benign prostate cancer cells, making it a potential marker for assessing prostate cancer when identified in serum and urine samples. 14 , 53 Plasma nuclear magnetic resonance (NMR) metabolic profiles have identified increased sarcosine concentrations in OSCC patients compared with controls 15 However, it was found at a low concentration in saliva of OSCC of humans compared with healthy controls, with an unknown mechanism. 54 In tumor studies of dogs, sarcosine exhibits significant downregulation in dogs with urothelial carcinoma of the bladder compared with those with urolithiasis, regardless of the presence of urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 Sarcosine has been implicated in promoting the malignant proliferation of benign prostate cancer cells, making it a potential marker for assessing prostate cancer when identified in serum and urine samples. 14 , 53 Plasma nuclear magnetic resonance (NMR) metabolic profiles have identified increased sarcosine concentrations in OSCC patients compared with controls 15 However, it was found at a low concentration in saliva of OSCC of humans compared with healthy controls, with an unknown mechanism. 54 In tumor studies of dogs, sarcosine exhibits significant downregulation in dogs with urothelial carcinoma of the bladder compared with those with urolithiasis, regardless of the presence of urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In recent years, salivary metabolomics has emerged as a diagnostic tool for various cancers in humans, including oral, breast, pancreatic, and prostatic cancers. 11 , 12 , 13 , 14 , 15 Aberrant metabolites in aminoacyl transfer RNA (tRNA) biosynthesis, arginine biosynthesis and metabolism, lysine degradation, histidine metabolism, and proline metabolism have been identified from precancerous stages in humans with OSCC. 16 One study demonstrated the ability of the combination of S‐adenosylmethionine and pipecolate from saliva samples to distinguish patients with oral cancers from healthy controls.…”
Section: Introductionmentioning
confidence: 99%